Recent advances in the management of neonatal jaundice - Watchko JF (Dove Medical Press, 2014)
Jon F Watchko Division of Newborn Medicine, Department of Pediatrics, University of Pittsburgh School of Medicine, Magee-Womens Research Institute, Pittsburgh, PA, USA Abstract: Advances in the clinical assessment strategies used to identify neonates at risk for the development of severe hyperbilirubinemia and bilirubin neurotoxicity, as well as the treatment measures to control hyperbilirubinemia in newborns, continue to be made. They include, among others, universal predischarge birth hospitalization bilirubin screening, the confirmation that hemolysis is an important risk factor for bilirubin neurotoxicity, the use of a numeric scoring system to help stage the severity of acute bilirubin encephalopathy, the potential advantages of turquoise-light phototherapy, and the potential role of heme-oxygenase inhibitors in preventing the need for exchange transfusions, all of which are reviewed here. Keywords: phototherapy, exchange transfusion, bilirubin, free bilirubin, bilirubin encephalopathy, kernicterus